2017
DOI: 10.1128/aem.00696-17
|View full text |Cite
|
Sign up to set email alerts
|

Simulated rRNA/DNA Ratios Show Potential To Misclassify Active Populations as Dormant

Abstract: The use of rRNA/DNA ratios derived from surveys of rRNA sequences in RNA and DNA extracts is an appealing but poorly validated approach to infer the activity status of environmental microbes. To improve the interpretation of rRNA/DNA ratios, we performed simulations to investigate the effects of community structure, rRNA amplification, and sampling depth on the accuracy of rRNA/DNA ratios in classifying bacterial populations as “active” or “dormant.” Community structure was an insignificant factor. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 50 publications
0
64
0
1
Order By: Relevance
“…For example, studies that characterize microbial communities using high-throughput DNA sequencing implicitly assume that primer coverage, extraction efficiency, and amplification bias do not prevent molecular surveys from reflecting actual community structure[49]. There are also assumptions regarding the relationship between growth rate and rRNA content, when making inferences about the metabolic activity of microbial taxa using 16S ribosomal DNA and RNA sequencing [50, 51]. However, these caveats and limitations can, in part, be addressed by coupling empirical efforts with models that explicitly encode hypothesized mechanisms and that are independent of methodological assumptions.…”
Section: Methodsmentioning
confidence: 99%
“…For example, studies that characterize microbial communities using high-throughput DNA sequencing implicitly assume that primer coverage, extraction efficiency, and amplification bias do not prevent molecular surveys from reflecting actual community structure[49]. There are also assumptions regarding the relationship between growth rate and rRNA content, when making inferences about the metabolic activity of microbial taxa using 16S ribosomal DNA and RNA sequencing [50, 51]. However, these caveats and limitations can, in part, be addressed by coupling empirical efforts with models that explicitly encode hypothesized mechanisms and that are independent of methodological assumptions.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, although rRNA:rDNA values larger 233 than one are frequently used as criteria for activity (Blazewicz, et al 2013), different taxa might differ 234 in their rRNA content during growth or dormancy to the extent that rRNA content and growth rate are 235 not linked (Blazewicz, et al 2013). Thus, potentially active taxa might be misclassified as dormant 236 just because their rRNA:rDNA ratio is below one (Steven, et al 2017). 237…”
Section: Sidestream and Mainstream Communities 180mentioning
confidence: 99%
“…The disproportionally high read abundances of rRNA at low rDNA abundances for most phyla 239 ( Figure S4) confirm previous similar observations, suggesting higher activity among rare taxa 240 (Campbell, et al 2011, Jia, et al 2019, Jones and Lennon 2010, Klein, et al 2016, Wilhelm, et al 241 2014. This phenomenon could perhaps be due to under-sampling (Steven, et al 2017), but higher 242 growth rate among rare taxa could arise due to intraspecific competition or predation of abundant taxa 243 (Jousset, et al 2017). In fact, by using metagenomic data, Jia, et al (2019) observed higher 244 replication rates for taxa at low relative abundances supporting that this is a real phenomenon.…”
mentioning
confidence: 99%
“…Taxa with 16S ratios greater than a specified threshold are considered ‘active’, and most studies report using a threshold of 1.0, which indicates more rRNA reads than rDNA reads for those taxa (6, 8, 16). One limitation to this approach is that using an arbitrary threshold to distinguish active from dormant taxa may be problematic in diverse communities (13, 17), given that rRNA production and growth rate are not necessarily always correlated (2429). Another challenge in assessing 16S ratios is the occurrence of ‘phantom taxa’: taxa that are detected in rRNA but not rDNA sequences (18) which leads to a zero-denominator (and thus undefined) 16S ratio.…”
Section: Introductionmentioning
confidence: 99%